Synthesis and biological evaluation of fused dipyranoquinolinones as inhibitors of acetylcholinesterase with antioxidant properties - Evangelia-Eirini N. Vlachou; Ioannis Fotopoulos; Catherine Gabriel; Eleni Pontiki; Dimitra J. Hadjipavlou-Litina; Konstantinos E. Litinas (European Journal of Medicinal Chemistry Reports, 2022)
Bis-fused pyridopyranocoumarins are prepared in excellent yields through the triple bond activation of propargylaminopropargyloxycoumarins or propargylamino (Kontogiorgis et al., 2012; Zhang et al., 2014) [7,8]-fused pyranocoumarins by gold nanoparticles supported on TiO2 under microwave irradiation. The intermediate new propargylaminopropargyloxycoumarins are synthesized through propargylation of 6-amino-7-hydroxycoumarins or 6-amino-4-hydroxycoumarin. Preliminary biological tests indicated remarkable antioxidant and anti-AChE activities of the new compounds and especially for 16a and 19b which present also druglikeness following the rule of five.